Upravne radnje i službena evidencija u organima uprave / Administrative Actions and Official Record Keeping within Administration Bodies - Ajanović, Enver (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
In the Socialist Federal Republic of Yugoslavia administrative law theory, the concept of a substantive administrative act included documenting, notifying, receiving statements, and other substantive acts of administration. From such a division it is evident that those terms do not clearly distinguish between legal statics and legal dynamics. Furthermore, the notion of substantive administrative acts cannot be found in legal lexicons, so it should not be used in the theory of administrative law. In accordance with the findings showing that such term is of foreign linguistic origin, in the contemporary BH administrative law theory, it is necessary to use the administrative action term as a procedural precondition for the emergence of different official records of data within administrative bodies. This conceptual renewal in the administrative law theory provides a more easy to perceive, understand, or interpret idea of ​​ administrative action, official records and administrative act interconnectedness. Both French and German administrative laws have terms operation administratif and Tathandlung or Realakt and can be translated as administrative action from French and material action from German. In SFRY, the concept of a substantive administration act is not sufficiently theoretically explained. After signing the Dayton Peace Accords, new sorts of data emerged in the administrative and legal order, and the administrative act became a measure for regulating market and private legal relations as well.